A mechanical model for sheared joints based on Mohr-Coulomb material properties. Issue 2 (19th April 2018) - Han, J.; Liang, H.; Cao, C.; Bi, Z.; Zhu, Z.
Abstract : This paper presents a mechanical model for sheared rock joints using microstructural analysis of asperity damage. The shear resistance of the rock joint is formulated as a function of the geometry of the rock joint, Mohr-Coulomb mechanical properties of the materials and the loading levels. Deformation of the rock joints can be classified as slip at the joint faces, and partial and complete shearing off of the asperity. The theoretical implications of the mechanical model developed have also been corroborated by relevant experimental data in the literature.